Effectiveness, safety and treatment adherence of biosimilar follow‐on insulin in diabetes management. Issue 10 (28th June 2022) - Pham, Timothy T.; Chen, Xiaoxue; Barron, John; Hart, Richard; Abarca, Jacob; DeVries, Andrea
Abstract: Aim: To assess the change in HbA1c after initiation of biosimilar follow‐on insulin (Basaglar) or reference insulin (Lantus) among patients with type 2 diabetes. We also compared treatment adherence, safety events and costs at 1 year after initiation of insulin. Materials and Methods: Using claims data from a large US health plan during 2016‐2020, we identified adults with type 2 diabetes who initiated either Basaglar or Lantus. Generalized linear regression modelling assessed the differences in outcomes between the two groups. A 0.4% margin was used to determine non‐inferiority for HbA1c. Results: The study included 1136 Basaglar users and 6304 Lantus users. Both Lantus and Basaglar groups showed more than 1% reduction in HbA1c over 6 months and over 12 months. Reduction in HbA1c with Basaglar was similar (non‐inferior) to that with Lantus, with an adjusted difference of Basaglar to Lantus of 0.14% (95% CI −0.02 to 0.30) over 6 months and 0.17% (95% CI 0.02 to 0.32) over 12 months. Rates of adverse events were similar for both hypoglycaemia and vascular events. The Basaglar group showed higher adherence in terms of proportion of days covered (adjusted difference 0.06, 95% CI 0.04 to 0.08). Medical costs were similar, but the cost of Basaglar was lower (adjusted mean cost difference −$462, 95% CI −$556 to −$363) after adjustment. Conclusions: In patients with type 2 diabetes, Basaglar provided similar glycaemic control compared with Lantus, had a similar safety profile and lower drug costs, and showed more favourable adherence.